Analysis of the need for biotechnology research on cassava, yam, and plantain - Asiedu, Robert; Ng, S.; Vuylsteke, D.R.; Terauchi, R.; Hahn, S. (1992)
Cassava, yam, and plantain are staple food crops essential to food security in the humid and Sub-humid tropics of Africa. However, these crops have long growth cycles, high perishability and slow multiplication rates of propagation materials, and they are subject to a number of biological stresses. These stresses include diseases, insects, mites, nematodes, and weeds. There are gaps in our knowledge, especially in the area of genetics, which influence the pace of breeding. Intensification of research is needed in cytogenetics, molecular genetics, in vitro culture, cry op reservation, and disease diagnosis.